2011
DOI: 10.5535/arm.2011.35.4.460
|View full text |Cite
|
Sign up to set email alerts
|

The Factors Associated with Good Responses to Speech Therapy Combined with Transcranial Direct Current Stimulation in Post-stroke Aphasic Patients

Abstract: ObjectiveTo determine factors associated with good responses to speech therapy combined with transcranial direct current stimulation (tDCS) in aphasic patients after stroke.MethodThe language function was evaluated using Korean version of Western aphasia battery (K-WAB) before and after speech therapy with tDCS in 37 stroke patients. Patients received speech therapy for 30 minutes over 2 to 3 weeks (10 sessions) while the cathodal tDCS was performed to the Brodmann area 45 with 1 mA for 20 minutes. We compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 29 publications
(41 reference statements)
5
61
0
7
Order By: Relevance
“…In the past decade, researchers have investigated the use of noninvasive neuromodulation techniques and, in particular, transcranial direct current stimulation (tDCS) to promote language recovery in poststroke aphasia [3]. While the first published study [4] that documented tDCS use for aphasia rehabilitation did not include a behavioral treatment protocol, studies since then have combined tDCS with speech-language therapy [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. These initial studies generally included behavioral treatment for anomia and implemented noun retrieval as the outcome measure; more recent studies have included additional behavioral treatments for the recovery of verbs [5,7,13], articulation [9] and discourse productivity [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, researchers have investigated the use of noninvasive neuromodulation techniques and, in particular, transcranial direct current stimulation (tDCS) to promote language recovery in poststroke aphasia [3]. While the first published study [4] that documented tDCS use for aphasia rehabilitation did not include a behavioral treatment protocol, studies since then have combined tDCS with speech-language therapy [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. These initial studies generally included behavioral treatment for anomia and implemented noun retrieval as the outcome measure; more recent studies have included additional behavioral treatments for the recovery of verbs [5,7,13], articulation [9] and discourse productivity [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…These studies all showed positive effects of tDCS on participants' language performance (see reviews by Floel, 2013, andMonti et al, 2012). Some studies also highlighted the influence of the severity of baseline naming deficits on the effect size of tDCS-induced improvements (e.g., Floel et al, 2012;Jung et al, 2011). In terms of language, tDCS has been shown to improve various language abilities such as word acquisition (Floel et al, 2012), production (Iyer et al, 2005), and retrieval (Fiori et al, 2011), depending on stimulation parameters such as stimulation site, dosage, and participants' initial language abilities.…”
Section: Language Cognitionmentioning
confidence: 95%
“…For example, Jung et al (2011) investigated the factors associated with better results when combining tDCS with speech therapy. They found that patients who received C-tDCS over the right IFG improved significantly in terms of the aphasia quotient.…”
Section: Optimizing the Effects Of Tdcs For Cognitive Enhancementmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies of chronic stroke, anodal tDCS applied to the structurally intact perilesional left cortex facilitated naming performance post treatment [86-88, 89••]. In acute stroke, tDCS was used to stimulate the right hemisphere to improve spontaneous speech, auditory verbal comprehension, and test performance as reflected by aphasia quotients [90,91].…”
Section: Neuromodulationmentioning
confidence: 99%